KOMPETENSI PETERNAK SAPI POTONG PERANAKAN ONGOLE DALAM PEMBUATAN KOMPOS (STUDI KASUS PADA KELOMPOK TERNAK MEKAR KECAMATAN DAGANGAN KABUPATEN MADIUN) - Deha Purwoko; Bekti Nur Utami (University of Jember, 2017)
This research aims to describe the level of competence of farmers in composting, and to draft extension and try out the implementation of counseling about composting in group of livestock of Mekar. The research was conducted in sub-district Dagangan of Madiun Regency. Selection of livestock group is done by purposive that is the only group of livestock that have made compost that is group of livestock of Mekar which is located in Kepet village. The research method used is case study with quantitative descriptive approach with scoring. The population is 44 people, the sample is based on the census. The results showed that: 1) the level of competence of farmers in composting is classified with the details of the competence of the preparation stage is low, the competence of the manufacturing process is low, and the competence of the storage stage is classified; and 2) drafting the extension plan based on the target and the purpose of extension so that the breeder know, understand and able to increase the C-Organic content and C / N Ratio on the compost according to the standard. Success shows the improvement of compost quality before and after counseling in accordance with the purpose of counseling. Keywords: competence of breeder, livestock group of Mekar, draft extension, composting, extension